Matrix-producing mammary carcinoma: A rare breast tumor - Mardi Kavita; Sharma Jaishree (Wolters Kluwer Medknow Publications, 2008)
Matrix-producing carcinoma of the breast is a unique subclass of metaplastic carcinoma which is characterized by the existence of a ductal carcinomatous component with direct transition to areas showing cartilagenous or osseous differentiation, lacking an interspersed spindle cell component. This article reports one such rare case in a 50-year-old woman who had a right breast mass. f0 ine needle aspiration (FNA) smears showed abundant chondromyxoid extracellular matrix to which were variably admixed carcinomatous cells. Histological examination revealed a neoplasm composed of invave ductal carcinoma with a direct transition to chondrosarcomatous areas. The case is reported not only for its peculiar microscopic characteristics but also to highlight its better prognostic features and hence, the need for its recognition.